Развитие методов расчета систем тягового электроснабжения и питающих их энергосистем - Доманский, И.В. (Електротехніка і електромеханіка, 2015)
Статья посвящена развитию методов расчета систем тягового электроснабжения с учетом питающих их энергосистем. Предложены алгоритмы формализации графов схем внешнего и тягового электроснабжения и методика
выбора параметров и мест размещения установок продольной компенсации. Стаття присвячена розвитку методів розрахунку систем тягового електропостачання з урахуванням енергосистем,
що їх живлять. Запропоновано алгоритми формалізації графів схем зовнішнього і тягового електропостачання та
методика вибору параметрів і місць розміщення установок поздовжньої компенсації. Currently, the cause deterioration of quality rating of electricity
on tire traction substations AC can be either how mode of operation of power systems, industrial loads so and the impact of
electric traction. The experience of energy surveys show that the
loss from flow potential equalization currents in each the third
plot between traction substations AC is amount to not less than
250 thousand kW·h per year. To select the optimum power and
places location of the device longitudinal capacitive of compensation and decision other tasks it is necessary methodology of
systems of calculation that takes into account the complex nature of the mutual influence of the quality of the electricity coming from the energy system of and the transportation process. In
the paper proposed three options for calculation algorithms
modes work of existing and perspective systems, traction power
supply AC jointly with power supply their by energy systems,
including the algorithm for calculating networks of different
nominal voltages using the transformations; decomposition and
synthesis of networks with different voltage levels; the iterations
and probabilistic assessment of the impact of power mains. Developed the schemes formalization of graphs and the matrices of
portions of the outer and traction power supply and method of
selecting parameters and places location of the devices longitudinal capacitive of compensation, which are based on direct
methods solving systems of linear algebraic equations with a
dense banded and profile-sparse the matrix. Are generalized
ways of formation and transformation of graphs of schemes
traction power supply and feeding them energy systems and
proposed the method of calculation the complex the moment of
schemes, which increases the accuracy of calculating of flows
power on traction networks to 1-2 % and allows you to select
the optimal parameters and places location of the devices longitudinal capacitive of compensation. Analysis of the results of
modeling and real modes of traction network shows that the
efficiency of use longitudinal capacitive compensation is high on
traction substations for which the resistance external electric
power supply system of the is greater than 0.5 ohms, and the
degree of compensation is within the allowable K = 0.7.